Non-parametric performance evaluation of container ports - Munisamy, S.; Danxia, W. (2011)
This paper analyses the performance of major container ports in Asia using the non-parametric approach. Because of the known sensitivity of the traditional non-parametric approaches such as Data Envelopment Analysis (DEA) and Free Disposal Hull (FDH) to extreme values or outliers, small sample size and slow convergence rates of efficiency estimates, this study employs an alternative robust non-parametric technique called order-m estimator following Cazals et al. (2002) to evaluate the efficiency of container ports. In this study, we conduct two analyses comprising order-m and Free Disposal Hull (FDH), and rank the container ports with the order-m efficiency estimates. The estimates are robust with respect to outliers in the data.